A new species of the genus Comidoblemmus Storozhenko & Paik (Orthoptera: Gryllidae) from Xizang, China - Wu, Ling; Liu, Hao-Yu (Zootaxa, 2017)
A new species is described from China, Comidoblemmus yigongensis sp. nov. (Xizang: Bomi), which is illustrated with habitus, head and supra anal plate of both sexes and genitalia of male. A key for identification of all species of the genus Comidoblemmus is presented.